2002 23rd International Conference on Microelectronics. Proceedings (Cat. No.02TH8595)
DOI: 10.1109/miel.2002.1003197
|View full text |Cite
|
Sign up to set email alerts
|

Phase noise amplitude distribution as indicator of origin of random phase perturbation in a test oscillator

Abstract: In this paper we present an analysis of phase noise distribution. Phase noise, of designed and realized test oscillator, as a consequence of low frequency (LF) noise up-conversion was simulated. The analysis shows that low frequency noise sources, which are inside of transistor, give the pure Gaussian distribution of phase noise and LF noise sources located out of transistor change this distribution. This behavior could be explained by the influence of transistors and transistor's package impedance, which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…J.H. Vukovic et al also reported on phase noise distribution, stating that intrinsic perturbations originating from transistors in electronic oscillators produce a pure Gaussian distribution, while perturbations from active elements change the Gaussian distribution to an exponential one [ 16 ]. However, it was noted that their pure Gaussian distribution for the intrinsic perturbation case could be fitted with a mixture of Gaussian probability density functions.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
“…J.H. Vukovic et al also reported on phase noise distribution, stating that intrinsic perturbations originating from transistors in electronic oscillators produce a pure Gaussian distribution, while perturbations from active elements change the Gaussian distribution to an exponential one [ 16 ]. However, it was noted that their pure Gaussian distribution for the intrinsic perturbation case could be fitted with a mixture of Gaussian probability density functions.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%